Enhancing Arabic vocabulary mastery through augmented reality: a study on AR-MUFRADAT application for primary school students - Lily Hanefarezan, Asbulah; Nur Syahiirah Izan, Azihan; Mohamad Hilman, Nordin *; Mus'ab, Sahrim (2024)
The advancement of modern technology has greatly influenced national development, with technologies like Augmented Reality (AR) increasingly integrated into education in Malaysia and Indonesia. Despite this, no study has yet explored the specific need for AR technology in teaching Arabic vocabulary from the KSSR syllabus in primary schools. Currently, students rely on traditional teaching methods, which limit their learning experience. This study investigates the need for AR-Mufradat development among Year 5 students at Sri Al-Amin Bangi Primary School. A quantitative approach was used, involving 30 students as respondents, and data was collected through a survey. The findings, analyzed using SPSS version 26, reveal a high demand for AR-Mufradat among these students. This study aims to guide future research, suggesting that AR technology could enhance the teaching and learning of Arabic, allowing students to master the language more effectively.